(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aimed to find out the extent of success achieved by the Saudi channel in the aspect of family education programs mainly by students of the Department of Media at King Faisal University, in addition to knowing the viewing habits of the Saudi channel by the study sample, where the study relied on the analytical survey method, and on the questionnaire tool mainly by applying to a sample of (272) individual students of the Media Department at the Faculty of Arts at King Faisal University, and the study reached several results, the most important of which are the study found that the majority of the sample members watch the channel weekly from once to twice by 78.3%, and also the study found that 70.6% of the sample members spend less than an hour a week watching the channel, and the study found that the majority of the sample members watch the channel with the family and by 81.3%, and also the study reached a number of recommendations, the most important of which is that The Saudi channel should pay attention to family culture issues that were low in interest by the channel, and the study also recommended choosing high-viewership times to publish.